(untitled) (Research, Society and Development, 2021)
The supervised teaching internship is of great importance for the licensee, becoming an opportunity to have contact with their future work environment. The construction of the teacher’s identity cannot and should not be considered only due to the theoretical knowledge acquired throughout their training, with the teaching internship being the culmination of the initial teacher training process. In this sense, the purpose of this work is to report, the experiences lived by undergraduate students in the supervised teaching stage in biology, and their contributions to teacher education. During the coexistence, important points for the formation of a good professional were analyzed, such as the teacher’s posture and the ability to identify the needs of the students and the class as a whole. The internship is an important and indispensable process for teacher training. It enabled the assimilation of theory and practice, because through it the licensee experienced conflicts and difficulties faced in the classroom. With the internship, the future professional was able to learn about the dynamics of the school, the process of planning and conducting classes, the behavior of students in the classroom and the day-to-day life of the profession. Thus, it was evident that this moment is of fundamental importance for the future teacher.